Aggressive and nonaggressive translocation t(6;11) renal cell carcinoma: comparative study of 6 cases and review of the literature - Peckova, Kvetoslava; Vanecek, Tomas; Martinek, Petr; Spagnolo, Dominic; Kuroda, Naoto; Brunelli, Matteo; Vranic, Semir; Djuricic, Slavisa; Rotterova, Pavla; Daum, Ondrej; Kokoskova, Bohuslava; Vesela, Pavla; et al. (Annals of diagnostic pathology, 2014)
UNLABELLED: t(6;11) renal cell carcinoma (RCC) has been recognized as a rare and mostly nonaggressive tumor (NAT). The criteria for distinguishing aggressive tumors (AT) from NATs are not well established. A total of 6 cases were selected for the study. Five cases of t(6;11) RCCs behaved nonaggressively, and 1 was carcinoma with aggressive behavior. The tumors were analyzed morphologically using immunohistochemistry and by molecular-genetic methods. The specimen of aggressive t(6;11) RCC was from a 77-year-old woman who died of the disease 2.5 months after diagnosis. The specimens of nonaggressive t(6;11) RCCs were from 3 women and 2 men whose ages range between 15 and 54 years. Follow-up was available in all cases (2.5 months-8 years). The tumor size ranged from 3 to 14 cm in nonaggressive t(6;11) RCC. In the aggressive carcinoma, the tumor size was 12 cm. All tumors (6/6) were well circumscribed. Aggressive t(6;11) RCC was widely necrotic. Six (100%) of 6 all tumors displayed a solid/alveolar architecture with occasional tubules and pseudorosettes. Pseudopapillary formations lined by bizarre polymorphic cells were found focally in the aggressive t(6;11) RCC case. Mitoses, though rare, were found as well. All cases (AT and NAT) were positive for HMB-45, Melan-A, Cathepsin K, and cytokeratins. CD117 positivity was seen in 4 of 5 NATs, as well as in the primary and metastatic lesions of the AT. mTOR was positive in 2 of 5 NATs and vimentin in 4 of 5 NATs. Vimentin was negative in the primary lesion of the AT, as well as in the metastasis found in the adrenal gland. Translocation t(6;11)(Alpha-TFEB) or TFEB break was detected in 4 of 5 NATs and in the AT case. Aggressive tumor showed amplification of TFEB locus. Losses of part of chromosome 1 and chromosome 22 were found in 1 of 5 NATs and in the AT. CONCLUSIONS: (1) Aggressive t(6;11) RCCs generally occur in the older population in comparison with their indolent counterparts. (2) In regard to the histologic findings in ATs, 3 of 5 so far published cases were morphologically not typical for t(6;11) RCC. Of the 3 cases, 2 cases lacked a small cell component and 1 closely mimicked clear cell-type RCC. (3) Necroses were only present in aggressive t(6;11) RCC. (4) Amplification of TFEB locus was also found only in the aggressive t(6;11) RCC.
Keywords: Young Adult; nádory ledvin; Male; mladý dospělý; karcinom z renálních buněk; Adolescent; Molecular biology; transkripční faktory BHLH-Zip; Aggressive; Adult; Kidney Neoplasms; Age Factors; Kidney; Aged; dospělí; translokace genetická; mužské pohlaví; senioři; Chromosomes, Human, Pair 6; t(6; 11); mladiství; Translocation renal cell carcinoma; Nonaggressive; lidé; ženské pohlaví; Immunohistochemistry; Humans; lidské chromozomy, pár 6; lidské chromozomy, pár 11; věkové faktory; Translocation, Genetic; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Carcinoma, Renal Cell; Chromosomes, Human, Pair 11; Female; lidé středního věku; Middle Aged